Practical guidelines for peer support programmes for mental health problems - Campos, Filipa (2019)
Introduction: This study aims to determine the guiding principles for the implementation of peer support programmes in Portugal. Materials and methods: The study was divided in two phases. In the ﬁrst phase a systematic review of 112 papers indexed in ISI and EBSCO databases (2001---2012) was conducted. In the second phase clinicians, researchers, and people with psychiatric disabilities were invited to take part in a two-round online survey based on the Delphi process to rate the importance of statements generated from the systematic review. Data were analysed with NVIVO 9 and SPSS 19. Results: During the Delphi round 72 experts were contacted, 44 participated in the second round. A consensus was achieved on major statements, with 84% of the sentences obtaining a consensus and eight key recommendations covering goals of peer support, selection of peer supporters, training and accreditation, role of mental health professionals, role of peer sup-porters, access to peer supporters, looking after peer supporters, and programme evaluation were based on these statements. Conclusions: Use of peer support for mental heath problems is still underexplored and sur-rounded by some controversy and ambiguity. However, its organisation and proper monitoring appears to enhance the quality of life and social inclusion of people with mental illness. This highlights the importance of conducting studies that increase our knowledge of these pro-grammes and determining guidelines for their implementation. This national consensus may be used as a starting point for the design and implementation of peer support programmes in mental health organisations.